VAT gap determinants in the European Union and Poland - Pluskota, Anna (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: VAT revenues constitute a significant part of the budgets of EU countries and Poland. Both the EU and Poland are taking steps to reduce the VAT gap. To define the areas influencing the size of the VAT gap, its determinants should be indicated. Aim: The study aims to identify the determinants of the VAT gap in the EU and Poland. By comparing the impact of individual determinants on the VAT Gap in the EU and Poland, it will be possible to identify common factors shaping the VAT gap in the EU and Poland. Results: Based on the econometric study, it was indicated that growth, trade, consumption, and corruption are significant determinants of the VAT gap in the EU and Poland. However, it has been shown that the impact of consumption and corruption on the VAT gap in Poland is different from that in the EU.